Ethics in Human Subjects Research: Do Incentives Matter? - Grant, Ruth W.; Sugarman, Jeremy (The Journal of medicine and philosophy, 2004)
There is considerable confusion regarding the ethical appropriateness of using incentives in research with human subjects. Previous work on determining whether incentives are unethical considers them as a form of undue influence or coercive offer. We understand the ethical issue of undue influence as an issue, not of coercion, but of corruption of judgment. By doing so we find that, for the most part, the use of incentives to recruit and retain research subjects is innocuous. But there are some instances where it is not. Specifically, incentives become problematic when conjoined with the following factors, singly or in combination with one another: where the subject is in a dependency relationship with the researcher, where the risks are particularly high, where the research is degrading, where the participant will only consent if the incentive is relatively large because the participant's aversion to the study is strong, and where the aversion is a principled one. The factors we have identified and the kinds of judgments they require differ substantially from those considered crucial in most previous discussions of the ethics of employing incentives in research with human subjects.